The aesthetics of disability in literature: The Sound and the Fury by William Faulkner and The Secret Garden by Frances Hodgson Burnett - López Barrantes, Magaly (2024)
The following study analyzes disability as a writing technique to produce an aesthetic effect in Faulkner’s The Sound and the Fury (1929) and Burnett’s The Secret Garden (1911). Disability is a condition that has always been present in human history and multiple records show how societies dealt with people with disabilities in the past. For instance, some disabled subjects were confined to a domestic space while others were abandoned or killed. The ideology of the hegemonic group, the cultural individualism, and the principles of autonomy during the nineteenth century in the United States were elements that created a negative social representation of disability based on ideas of personal inadequacy and limitation. The disabled were seen as incomplete people who were incapable of reaching the social conventions of behavior and productivity. As a consequence, the ideas cultivated throughout the nineteenth century contributed to the limits imposed: “disabled people are often imagined as unable to be productive, direct their own lives, participate in community, or establish meaningful personal relations” (Garland-Thomson, Extraordinary Bodies 46). Thus, the stereotypes have made society diminish the importance of their accomplishments and emphasize their limitations. Garland-Thomson states that people with disabilities appeared in oral traditions and, afterwards, they became part of several literary texts over the years; for example, Tiny Tim in “A Christmas Carol,” Quasimodo in The Hunchback of Notre Dame, Lenny Small in Of Mice and Men, and Laura Wingfield in The Glass Menagerie are literary characters that portray common forms of disability in the world. Mental and physical disability have played many roles in literature; for instance, some characters were portrayed as freaks, monsters, non-humans, ignoramuses, and fools. However, that is an inaccurate representation of disabled individuals who possess many positive qualities that unfortunate stereotypes hide. The aim of this work is to show how disability has also been used in literature as a means to engage readers in the plot of the texts. Disabled characters have the capability of causing rejection and contempt from the audience but, at the same time, they can create a desire and a need to discover more about their life, spirit, and fate. Hence, this work analyzes the paradox of disability, how it produces an ambivalent reaction that oscillates between rejection and attraction. In addition, this work explores how disability challenges conceptions of normality to stand as a powerful literary element that captivates the attention and fascinates readers. However, this stylistic use of disability contributes to stereotype these characters in literature and in real life, and strengthens the dominant ideology that defines which ones are supposedly normal bodies. Hence, the topic was chosen in an attempt to expose the negative effects that disability used as a reader-engaging literary device generates in real life by perpetuating misconceptions and stereotypes about the disabled. One must not simple assume that this literary construction of disability limits its impact to the novels, but one must also consider the implications that it could have in the social inclusion and acceptance of the mentally and physically disabled person. Therefore, the study raises awareness about the social repercussions that this insensitive portrayal of disability has on the fight of disabled people for equality and for their right to be valued as productive members of society.